Catholicism, natural theology, and the gift of understanding - Pinsent, A (Baker Academic, 2024)
Since the Patristic era, the Catholic faith has acknowledged two kinds of theology, today called ‘natural’ and ‘supernatural’, corresponding to the diverse worlds of discourse about God without and with what is particular to Christian revelation. The Church also formally defends the teaching that the one true God, Creator and Lord, can be known with certitude by those things which have been made, by the natural light of human reason. Drawing from Aquinas, however, I argue that the deeper distinction of natural and supernatural theology is in terms of subjective understanding, especially the understanding associated with the gift of the Holy Spirit in the life of grace. Progress in natural theology today will need to focus on this difficult topic of understanding, while recognising that natural theology alone can never bridge the gap between God and ourselves.